Political interest, cognitive ability and personality: Determinants of voter turnout in Britain - Kevin Denny; Orla Doyle (University College Dublin, Department of Economics, 2005)
This paper uses longitudinal data from the National Cohort Development Study (NCDS) to investigate the determinants of voter turnout in the 1997 British General Election. It introduces measures of cognitive ability and personality into models of electoral participation and finds that firstly, their inclusion reduces the impact of education and secondly, that standard turnout models may be biased by the inclusion of the much used “interest in politics” measure. A bivariate probit model of turnout and interest then shows that individuals with high ability, an aggressive personality and a sense of civic duty are more likely to both turn out to vote and to have an interest in politics.
hdl:10197/174
Keywords: 330; Turnout; Education; Ability; Personality